Viejos y nuevos enfoques para el desarrollo de vacunas contra la tuberculosis. - H. Bercovier (VacciMonitor, 2000)
Do we need renewed efforts to develop new vaccines to fight tuberculosis? Epidemiological data show that the decrease of the already low incidence of tuberculosis has stopped in developed countries. In certain Western countries the incidence of tuberculosis has even increased in the last ten years. In Africa and in Asia, a high incidence of tuberculosis is found similar to that of the Western world in the 1930s. Can we predict from the history of tuberculosis in Western Europe that the epidemic of tuberculosis in developing countries has reached his peak or is still developing? Revisited data from Europe show that the epidemic of tuberculosis started at least three centuries before it reached its apogee in the middle of the 19th century. The reasons for the decrease of tuberculosis in the first half of the 20th century in the Western world are still not well understood. Will public health measures and proper antibiotic treatment reduce and stop tuberculosis in Africa and in Asia or will the incidence of tuberculosis increase? Our ability to control the spread of the disease is complicated by the appearance of antibiotic resistant strains and HIV. Therefore, a better understanding of the molecular basis for the interaction between the bacilli and the hosts is necessary for the development of improved approaches for treatment and immunization. Cellular immunity and delayed type hypersensitivity (DTH) are key processes in the course of mycobacterial infection and are involved in both primary and secondary infection as well as in the induction of protective immunity in the host. The different types of tuberculosis vaccines being reevaluated comprise: BCG with booster, oral BCG, modified BCG (multivalent), auxotrophic M. tuberculosis attenuated strains, M. tuberculosis secreted proteins or recombinant proteins with or without immunomodulators and DNA vaccines. These new vaccines inducing a good cellular immunity may contribute to the development of improved approaches for immunization and treatment.